A balanced orchestra program: analyses and rehearsal techniques for Haydn, Berlioz, Ravel, Bryce Craig, and Casey Cangelosi - Duffy, Paul (Kansas State University, 2014)
This report provides detailed analyses of several orchestral works. Current orchestras have striven to rejuvenate their programs by balancing canonical literature with newer or less familiar works; such a practice has become especially important in an age when audiences are dwindling and orchestras are disbanding. The works included in this report follow that balanced blueprint, including staples such as Haydn’s Symphony No. 103 in E-flat Major (the “Drumroll”) and Berlioz’s “Hungarian March” from The Damnation of Faust to new orchestrations of 20th century works, such as Bryce Craig’s arrangement of the toccata from Ravel’s Le Tombeau de Couperin, as well as works composed within the last six years, such as Casey Cangelosi’s Concerto for Marimba and Orchestra No. 2. Each work’s formal design is straightforward, and the technical skills required are not virtuosic. The chapters below explore each work from a historical, theoretical, and performance perspective.
Keywords: Orchestra; Symphony; Concert program; Music; Analysis; Rehearsal technique; Music (0413); Musical Performances (0943)